Business-IT alignment from operational level: empirical evidence from the Bank of Qingdao, China - Yang Bin (2020)
Business-IT Alignment (BITA) has long been a significant topic for scholars as well as enterprise managers especially in the Internet era. Although numerous studies have identified the factors influencing the aligning process and relationships between them and organization successes from strategic perspective, few consider the impact of these elements on employees’s performances from an operational level. To fill this gap, this thesis first discusses the state-of-art and the challenges of BITA in China’s city commercial banks (CCBs) and further develops a theoretical framework to empirically evaluate the BITA in China banking industry. Finally, some recommendations for improving the level of BITA in China’s CCBs are provided. Taking the Bank of Qingdao (BQD) as a sample, this thesis empirically examines BITA maturity model with the results that five factors including communication, IT competency/value measurement, IT governance, partnership, and IT skills are positively related to the BITA while IT scope and architecture are not significant. In addition, the moderating effect of service quality between BITA and employee’s working performance is also supported by the survey. This study also develops a new theoretical model namely, business-IT punctuated equilibrium alignment model (BIPEAM), based on life cycle theory and punctuated equilibrium theory to describe the alternately leading roles between business and IT strategies. This model may contribute towards the better understanding of the mechanism of business-IT strategic alignment process from a longitudinal perspective within an enterprise.